Lateral Facies and Permeability Changes in Upper Shoreface Sandstones, Berakas Syncline, Brunei Darussalam - Ovinda, Ovinda; Lambiase, Joseph J (Indonesian Journal on Geoscience, 2017)
DOI:Â 10.17014/ijog.4.1.11-20Several outcrops were studied to identify sedimentary facies and to analyze permeability distribution, through which an outcrop analogue for upper shoreface reservoirs can be established. Four facies were identified: upper shoreface, lower shoreface, offshore transition, and tidal ones. Stratigraphic correlation of eleven outcrops indicates that the upper shoreface sandstone is generally clean, well sorted, parallel, and planar cross laminated. The sand becomes thinner and pinches out to the northwest where the mud proportion increases within the sand. Muddier sand was deposited in a relatively low energy upper shoreface setting. The thickness of the upper shoreface reservoir sand generally is 5 m. It decreases to zero over approximately 1.3 km as the sand pinches out to the northwest. To the northeast, the thickness also decreases to 4 m over approximately 4 km. Permeability values are more variable laterally than vertically. The permeability distribution has an obvious relationship to the sedimentary facies and is mainly controlled by the proportion of mud and bioturbation. As the sand pinches out in the northwest, permeability decreases from 590 md to 97 md over 1 km. To the northeast, permeability also decreases to 152 md over approximately 4 km where the sand becomes highly bioturbated. These values indicate that the sands are of good to very good reservoir quality. It appears that there are no major barriers to the lateral flow of fluid within the upper shoreface sandstone.